2010
DOI: 10.1007/s00251-010-0494-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of heterozygosity in the β2-microglobulin region of chromosome 15 in primary human tumors

Abstract: Downregulation or total loss of HLA class I expression on tumor cells is known as a mechanism of cancer immune escape. Alterations of the HLA phenotype are frequently due to mutations affecting genes encoding the HLA class I heavy chains located on chromosome 6p21 or the β2-microglobulin (β2m) gene encoding the light chain of the HLA complex located on chromosome 15q21. Frequently irreversible total loss of HLA class I molecules is due to the coincidence of two molecular events, the mutation of one β2m gene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 34 publications
2
54
1
1
Order By: Relevance
“…Allelic losses of these regions, particularly in many human cancers including head and neck cancers were found in high frequency. It was reported that highest LOH frequency was observed in colorectal and bladder cancers; relatively low LOH frequency was observed in kidney cancer [19]. However, in our study while LOH was not observed in any patients at D6S273 and D6S473 markers, MSI was observed in two patients.…”
Section: Discussioncontrasting
confidence: 53%
“…Allelic losses of these regions, particularly in many human cancers including head and neck cancers were found in high frequency. It was reported that highest LOH frequency was observed in colorectal and bladder cancers; relatively low LOH frequency was observed in kidney cancer [19]. However, in our study while LOH was not observed in any patients at D6S273 and D6S473 markers, MSI was observed in two patients.…”
Section: Discussioncontrasting
confidence: 53%
“…Notably, loss of chromosome 15q material in melanoma is not a very rare event (37,38). Of 70 metastatic melanoma samples analyzed, 16% were positive for loss of heterozygosity in chromosome region 15q21-22 (39). In the near future, exome studies will provide more detailed information about the frequency of B2M gene mutations in melanoma metastases, which we expect to be lower than B2M allelic losses.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, tumor cells cannot recover the antigen presentation capacity and the tumor microenvironment retains tumor escape phenotype favoring cancer progression. ‘Hard’ HLA-I aberrations in tumors (LOH in chromosomes 6 or 15 and beta 2-microglobulin mutations) are in the range of 30–40% of human cancers [55, 56]. In order to restore HLA-I expression in human tumors with ‘hard’ lesions we have made a recombinant adenovirus carrying beta 2-microglobulin gene and demonstrated a recovery of HLA-I expression on tumor cells deficient in beta 2-microglobulin.…”
Section: How To Deal With ‘Hard’ Lesions? Gene Therapy and Alternativmentioning
confidence: 99%